Average Error: 0.3 → 0
Time: 8.2s
Precision: 64
$\frac{1}{\sqrt{x}}$
${x}^{\frac{-1}{2}}$
\frac{1}{\sqrt{x}}
{x}^{\frac{-1}{2}}
double f(double x) {
double r15123498 = 1.0;
double r15123499 = x;
double r15123500 = sqrt(r15123499);
double r15123501 = r15123498 / r15123500;
return r15123501;
}


double f(double x) {
double r15123502 = x;
double r15123503 = -0.5;
double r15123504 = pow(r15123502, r15123503);
return r15123504;
}



Try it out

Results

 In Out
Enter valid numbers for all inputs

Derivation

1. Initial program 0.3

$\frac{1}{\sqrt{x}}$
2. Using strategy rm
3. Applied pow10.3

$\leadsto \frac{1}{\sqrt{\color{blue}{{x}^{1}}}}$
4. Applied sqrt-pow10.3

$\leadsto \frac{1}{\color{blue}{{x}^{\left(\frac{1}{2}\right)}}}$
5. Applied pow-flip0

$\leadsto \color{blue}{{x}^{\left(-\frac{1}{2}\right)}}$
6. Simplified0

$\leadsto {x}^{\color{blue}{\frac{-1}{2}}}$
7. Final simplification0

$\leadsto {x}^{\frac{-1}{2}}$

Reproduce

herbie shell --seed 1
(FPCore (x)
:name "1/sqrt(x)"
(/ 1 (sqrt x)))